Effects of the fatty acid synthase inhibitors triclosan and lapatinib on dengue virus and Zika virus infection - Suthatta Sornprasert; Janejira Jaratsittisin; Chanida Chumchanchira; Duncan R. Smith (Scientific Reports)
Abstract Fatty acid synthase (FASN) has been shown to be critical in the replication of several viruses of the genus Orthoflavivirus. In this study the role two inhibitors of FASN that work through different mechanisms were investigated in dengue virus (DENV) and Zika virus (ZIKV) infections. Triclosan is a FASN inhibitor that targets the enol reductase domain of FASN, while lapatinib exerts an effect on FASN through acting on HER2, an upstream regulator of FASN. After determining cytotoxicity, a comprehensive analysis of the effect of these drugs in DENV 2 and ZIKV infection was undertaken. The results showed that triclosan had moderate antiviral activity against both DENV 2 (EC50 = 10.21 µM; Selective index (SI) = 3.99) and ZIKV ( EC50 = 22.84 µM; SI = 5.49). Lapatinib had reasonable activity against DENV 2 (EC50 = 4.9 µM; SI = 26.09), but computer modeling suggested that lapatinib had the potential to be a directly acting antiviral by binding to NS5. The result of that analysis suggested that lapatinib was a better fit with ZIKV NS5 than DENV NS5, and this was confirmed as the EC50 for lapatinib towards ZIKV was was 2 µM and the calculated SI was 37.92. The results of triclosan are consistent with other studies that use inhibitors that target other domains of FASN, suggesting that simply targeting the enzymatic activity of FASN is insufficient for therapeutic drug development, but that lapatinib, or similar molecules may have real therapeutic potential.